TECHNOLOGICAL MODERNIZATION INTO THE ASPECT OF INDUSTRIAL AND INNOVATIVE DEVELOPMENTS OF ECONOMIC OF THE REPUBLIC OF KAZAKHSTAN (Journal of Economic Research & Business Administration, 2015)
In this article are considered questions of the extent of industrial sector of Kazakhstan economy, the level of its efficiency and the degree of its technologization are defined.